The Role Of Admission Officers In Providing General Consent Explanations To Inpatients At RSAD TK. II Udayana - Ni Kadek Suwiyani Kadek; A.A Gde Oka Widana; Ika Setya Purwanti (International Journal of Health Engineering and Technology, 2026)
Healthcare services in hospitals are required to uphold patient rights, one of which is through the provision of general consent. At RSAD TK. II Udayana, there were indications that the general consent explanation process was not optimal, as officers often requested signatures without providing adequate information regarding the contents and purpose of the consent. This study aims to find out the perceptions of medical records officers regarding their expectations of providing general consent explanations to inpatients at RSAD TK. II Udayana, analysed from the aspects of input, process, and output. This research is a qualitative study with a descriptive approach, where data were collected through in-depth interviews with staff and the head of the admission unit. The results showed that in the input aspect, most officers understood the function of general consent as legal protection. In the process aspect, officers provided explanations by adapting to the patient's communication needs following the registration flow. In the output aspect, officers played a role in ensuring administrative completeness via Electronic Medical Records (EMR) and handling consent refusals when necessary. In conclusion, the role of medical record officers at RSAD TK. II Udayana is generally well-implemented, but continuous supervision and training are required to ensure that patient information rights are consistently fulfilled to improve service quality.